Translation changes everything theory and practice - Venuti, Lawrence (Routledge, 2013)
"In Translation Changes Everything leading theorist Lawrence Venuti gathers fourteen of his incisive essays since 2000. The selection sketches the trajectory of his thinking about translation while engaging with the main trends in research and commentary. The issues covered include basic concepts like equivalence, retranslation, and reader reception; sociological topics like the impact of translations in the academy and the global cultural economy; and philosophical problems such as the translator's unconscious and translation ethics. Every essay presents case studies that include Venuti's own translation projects, illuminating the connections between theoretical concepts and verbal choices. The texts, drawn from a broad variety of languages, are both humanistic and pragmatic, encompassing such forms as poems and novels, religious and philosophical works, travel guidebooks and advertisements. The discussions all explore practical applications, whether writing, publishing, reviewing, teaching or studying translations. Venuti's aim is to conceive of translation as an interpretive act with far-reaching social effects, at once enabled and constrained by specific cultural situations. This latest chapter in his developing work is essential reading for translators and students of translation alike."